(untitled) (Sahmiyya: Jurnal Ekonomi dan Bisnis, 2023)
The reason for this research is that there is no research that examines the direct influence of financial knowledge, financial attitudes, and financial behavior on increasing the economic level of micro business actors, especially in the small micro business group which has an important role in the Indonesian economy. This research is based on the aim of the researcher to understand the magnitude of the effect given in part (t) or together (f). between the variables of financial knowledge, financial attitudes, and financial behavior, towards increasing the economic level of micro business actors among traders at Batik Setono Pekalongan Market. Quantitative research method, used in this study and to collect data as a booster and statistical test material, used a questionnaire with Likert scale criteria. In taking the specimen, the slovin formula was used and obtained specimens of 63 respondents. The variables in this study consisted of financial knowledge, financial attitudes and financial behavior while the variables used were the increase in the economic level of micro business actors. Multiple linear statistical test analysis was used in this study with the help of the product and service solution statistical platform version 23. Based on the conclusions of the evidence obtained as a conclusion that financial knowledge and financial attitudes do not have a significant positive impact on increasing the economic level of micro business actors in the market trader class. Meanwhile, finance has a significant positive impact on the level of traders in the market economy. The magnitude of the impact given is based on the R square test, the value is 39.1%, which means that 60.9% is influenced by other factors.